2008
DOI: 10.1097/jgp.0b013e3181898081
|View full text |Cite
|
Sign up to set email alerts
|

Religious Participation and DSM-IV Disorders Among Older African Americans: Findings From the National Survey of American Life

Abstract: Objectives-This study examined the religious correlates of psychiatric disorders. Design-The analysis is based on the National Survey of American Life (NSAL). The AfricanAmerican sample of the NSAL is a national representative sample of households with at least one African American adult 18 years or over. This study utilizes the older African American sub-sample (n=837).Methods-Religious correlates of selected measures of lifetime DSM-IV psychiatric disorders (i.e., panic disorder, agoraphobia, social phobia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
69
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 32 publications
8
69
2
1
Order By: Relevance
“…Moreover, even though we modeled important stress resiliency factors including sleep, recovery, and social support, other important factors, such as individual coping styles and participation in religious and voluntary organizations, were not measured. 42,43 Fatigue played an important role in the relationship between stress and perceived health. It fully mediated this relationship, which could mean that stress may lead to poor health outcomes when it is significant enough to drain stress resiliency resources and manifest as fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, even though we modeled important stress resiliency factors including sleep, recovery, and social support, other important factors, such as individual coping styles and participation in religious and voluntary organizations, were not measured. 42,43 Fatigue played an important role in the relationship between stress and perceived health. It fully mediated this relationship, which could mean that stress may lead to poor health outcomes when it is significant enough to drain stress resiliency resources and manifest as fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven of the 19 studies examined a geriatric sample [34][35][36][37][38][39][40][41][42][43][44], four papers focused on adolescents [45][46][47][48], and four studies examined adults [49][50][51][52]. Four focused on depression in the medically ill [34][35][36]42], two on religious coping [35,52], two had only female participants [34,46], and two examined on mother-offspring relationships [45,47].…”
Section: Depressionmentioning
confidence: 99%
“…In contrast, private prayer/Bible reading was unrelated to depression, and religious TV/radio listening was positively related with depression. Finally, Chatters et al [44] examined data on religious involvement and depression from the National Survey of American Life, using a subsample of African American aged 55 years or older; results indicated that religious service attendance was significantly and inversely associated with the likelihood of having a lifetime mood disorder.…”
Section: Depressionmentioning
confidence: 99%
“…Research of the relationship between R/S and depression is the most developed. Eleven of the 19 studies examined a geriatric sample [34][35][36][37][38][39][40][41][42][43][44], four papers focused on adolescents [45][46][47][48], and four studies examined adults [49][50][51][52]. Four focused on depression in the medically ill [34][35][36][37][38][39][40][41][42], two on religious coping [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52], two had only female participants [34][35][36]…”
Section: Depressionmentioning
confidence: 99%
“…Four focused on depression in the medically ill [34][35][36][37][38][39][40][41][42], two on religious coping [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52], two had only female participants [34][35][36][37][38][39][40][41][42][43][44][45][46], and two examined on mother-offspring relationships [45][46][47]. Five of the 19 studies examined psychiatric patients [36][37][38][39][40][41][42]...…”
Section: Depressionmentioning
confidence: 99%